2020
DOI: 10.3390/en13051123
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Fault Ride-Through Method in Power Distribution Systems with Distributed Generations Based on PCS

Abstract: The current practice of Distributed Generation (DG) disconnection for every fault in distribution systems has an adverse effect on utility and stable power trading when the penetration level of DGs is high. That is, in the process of fault detecting and Circuit Breaker (CB) reclosing when a temporary fault occurs, DGs should be disconnected from the Point of Common Coupling (PCC) before CB reclosing. Then all DGs should wait at least 5 minutes after restoration for reconnection and cannot supply the pre-bid po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A temporary fault ride-through technique has been presented for power distribution systems with DG units based on power conditioning systems (PCS) [157]. The authors identified the disconnection of DG units for every fault in DNs as an adverse development on the utility and steady power exchange and trading when integrating a large-scale distributed generator.…”
Section: Recent Trends In Dn With Dg and Future Directions 51 Recent Research On Grid-integrated Systemsmentioning
confidence: 99%
“…A temporary fault ride-through technique has been presented for power distribution systems with DG units based on power conditioning systems (PCS) [157]. The authors identified the disconnection of DG units for every fault in DNs as an adverse development on the utility and steady power exchange and trading when integrating a large-scale distributed generator.…”
Section: Recent Trends In Dn With Dg and Future Directions 51 Recent Research On Grid-integrated Systemsmentioning
confidence: 99%
“…The tendency of power flows to the distribution system is diversified by increasing distributed resources such as various DGs and electric vehicles [1,2]. Problems that affect line utilization include over-voltage and low-voltage occurring on the line and excess capacity of distribution line [3,4].…”
Section: Introductionmentioning
confidence: 99%